Optimal inclusion levels of palm kernel cake in diets for large and small ruminants: a meta-analysis - Fhonna, Fenda Alvionita; Jayanegara, Anuraga; Wajizah, Sitti; Samsudin, Anjas Asmara; Samadi, Samadi (Walter de Gruyter GmbH, 2026)
Inclusion of palm kernel cake (PKC) in ruminant diets is limited mainly due to inconsistent findings on its effects and optimal level. This meta-Analysis evaluated the effects of PKC inclusion on performance, nutrient intake, nutrient digestibility, rumen fermentation, carcass traits, and milk production, and determined its optimal levels. A total of 51 papers were systematically selected from Google Scholar, ScienceDirect, and Springer Link following the PRISMA guidelines. The dataset was analyzed using the PROC MIXED procedure in SAS® OnDemand for Academics, with study variation treated as random effects, and PKC inclusion level as fixed effects. In large ruminants, PKC inclusion exhibited a quadratic effect (p < 0.05) on crude protein intake (CPI), dry matter digestibility (DMD), and crude protein digestibility (CPD). However, dry matter intake (DMI) and average daily gain (ADG) were unaffected (p > 0.05). In small ruminants, PKC inclusion had no significant effect (p > 0.05) on DMI and CPI. Nonetheless, it exhibits a quadratic influence on ADG (p < 0.05). Optimal inclusion levels were defined as those providing the best production response (highest ADG and lowest FCR) while maintaining stable nutrient utilization. Optimal inclusion levels were identified as 106 g/kg DM (small ruminants) and 115 g/kg DM (goats) based on ADG, 139 g/kg DM (small ruminants) and 101 g/kg DM (sheep) based on feed conversion ratio (FCR), and 65 g/kg DM (dairy cattle) based on DMI. Optimal PKC inclusion levels maintain stable intake, growth performance, and production in both large and small ruminants despite its low palatability, whereas excessive levels may impair overall utilization. These findings provide evidence-based guidance for optimizing PKC use in ruminant diets and advancing sustainable livestock production systems.